2019
DOI: 10.1155/2019/9459103
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of “Cough-Trick” for Pain Relief during Venipuncture: An Experimental Crossover Investigation in Healthy Volunteers

Abstract: Objectives. The easily performed “cough-trick” (CT) reduces pain during venipuncture (VP), although the underlying mechanism remains unclear. The aim was to investigate the pain-reducing effect of CT during VP in comparison with two distraction methods, as well as under the influence of naloxone. Methods. 54 healthy male volunteers participated in 3 investigations. Pain during standardized VP with CT was compared to a “weak” distraction (squeezing a rubber ball; investigation 1; n=20) and to a “strong” distrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Injection method I: Before receiving the subcutaneous LMWH injection, the patient was asked to take a deep breath and cough once with moderate intensity to empty her/his lungs. After 10 seconds, the patient was asked to take a deep breath and cough a second time with the same intensity ( 20 ),( 22 )-( 23 ) . During the second cough, the needle was inserted into the tissue.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Injection method I: Before receiving the subcutaneous LMWH injection, the patient was asked to take a deep breath and cough once with moderate intensity to empty her/his lungs. After 10 seconds, the patient was asked to take a deep breath and cough a second time with the same intensity ( 20 ),( 22 )-( 23 ) . During the second cough, the needle was inserted into the tissue.…”
Section: Methodsmentioning
confidence: 99%
“…The coughing technique increases intrathoracic pressure and stimulation of the autonomic nervous system, thereby causing an increase in heart rate and blood pressure, a higher level of pressure in the subarachnoid space and baroreceptor activation ( 20 )-( 21 ) . The increase in pressure in the subarachnoid space brings the segmental pain prevention pathways into action, and this has the effect of reducing the perception of pain ( 20 ),( 22 ) . It has also been reported that as a result of the Valsalva maneuver, this technique has an antinociceptive effect, reducing the perception of pain in connection with vagal nerve stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have found increases in sAA and perceived stress levels from baseline in patients subjected to the acute stress associated with venipuncture [ 21 , 28 ], which is in agreement with our results. Meanwhile, several other studies have also examined the association between hemodynamic changes and needle pain [ 29 , 30 ]. In those studies, there were no significant changes in hemodynamic variables in the control groups before and after PIC, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%